Tìm y
y - (1/4 + 1/8) = 5/8 y x 3/4 = 1/5 x 9/8
y : 1/7 = 2/3 : 1 1/2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(y.3\dfrac{7}{12}=6\dfrac{1}{4}\)
\(y.\dfrac{43}{12}=\dfrac{25}{4}\)
\(y=\dfrac{25}{4}:\dfrac{43}{12}\)
\(y=\dfrac{25.12}{4.43}\)
\(y=\dfrac{75}{43}\)
\(a,\dfrac{-1}{8}=\dfrac{3}{x}\\ \dfrac{3}{-24}=\dfrac{3}{x}\\ x=-24\\ b,\dfrac{x}{3}=\dfrac{3}{x}\\ x.x=3.3\\ x^2=9\\ x=\pm3\\ c,\dfrac{3}{4}.x=1\dfrac{1}{2}\\ \dfrac{3}{4}.x=\dfrac{3}{2}\\ x=\dfrac{3}{2}:\dfrac{3}{4}\\ x=2\\ d,x-\dfrac{3}{10}=\dfrac{7}{15}:\dfrac{3}{5}\\ x-\dfrac{3}{10}=\dfrac{7}{9}\\ x=\dfrac{7}{9}+\dfrac{3}{10}\\ x=\dfrac{97}{90}\\ e,\dfrac{-4}{7}-x=\dfrac{-8}{3}.\dfrac{3}{7}\\ \dfrac{-4}{7}-x=\dfrac{-8}{7}\\ x=\dfrac{-4}{7}+\dfrac{8}{7}\\ x=\dfrac{4}{7}\\ \)
\(a,x-\dfrac{3}{4}=\dfrac{1}{7}\\ x=\dfrac{1}{7}+\dfrac{3}{4}\\ x=\dfrac{25}{28}\\ b,x+\dfrac{7}{5}=\dfrac{9}{8}.\dfrac{4}{27}\\ x+\dfrac{7}{5}=\dfrac{1}{6}\\ x=\dfrac{1}{6}-\dfrac{7}{5}\\ x=\dfrac{-37}{30}\\ c,\dfrac{2}{5}-\dfrac{3}{7}=\dfrac{x}{70}\\ \dfrac{-1}{35}=\dfrac{x}{70}\\ \dfrac{-2}{70}=\dfrac{x}{70}\\ x=-2\\ d,\dfrac{2}{9}-\dfrac{7}{8}.x=1\\ \dfrac{7}{8}.x=\dfrac{2}{9}-1\\ \dfrac{7}{8}.x=\dfrac{-7}{9}\\ x=\dfrac{-7}{9}:\dfrac{7}{8}\\ x=\dfrac{-8}{9}\)
\(a,x-\dfrac{3}{4}=\dfrac{1}{7}\)
\(\Rightarrow x=\dfrac{1}{7}+\dfrac{3}{4}\)
\(\Rightarrow x=\dfrac{25}{28}\)
\(b,x+\dfrac{7}{5}=\dfrac{9}{8}.\dfrac{4}{27}\)
\(\Rightarrow x+\dfrac{7}{5}=\dfrac{1}{6}\)
\(\Rightarrow x=\dfrac{1}{6}-\dfrac{7}{5}\)
\(\Rightarrow x=-\dfrac{37}{30}\)
\(c,\dfrac{2}{5}-\dfrac{3}{7}=\dfrac{x}{70}\)
\(\Rightarrow\dfrac{-1}{35}=\dfrac{x}{70}\)
\(\Rightarrow35x=-70\)
\(\Rightarrow x=-2\)
\(d,\dfrac{2}{9}-\dfrac{7}{8}.x=1\)
\(\Rightarrow\dfrac{7}{8}x=\dfrac{2}{9}-1\)
\(\Rightarrow\dfrac{7}{8}x=-\dfrac{7}{9}\)
\(\Rightarrow x=-\dfrac{8}{9}\)
a: x*3/4=1/5
=>x=1/5:3/4=1/5*4/3=4/15
b: x*3/7=2/5
=>x=2/5:3/7=2/5*7/3=14/15
c: 1/3+2/9=2/12x
=>1/6x=3/9+2/9=5/9
=>x=5/9*6=30/9=10/3
d: 4/15*x-2/3=1/5
=>4/15*x=2/3+1/5=10/15+3/15=13/15
=>4x=13
=>x=13/4
e: x:1/7=2/3
=>x=2/3*1/7=2/21
f: 1/9:x=7/3
=>x=1/9:7/3=1/9*3/7=3/63=1/21
j: 1/4+5/12=8/3:x
=>8/3:x=3/12+5/12=8/12=2/3
=>x=4
h: =>7/4:x=1/5+1/2=7/10
=>x=7/4:7/10=10/4=5/2
thankkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkkk
Bài 1: Tìm \(x\)
a; \(x-2\) + 7 = 1.3.(-9)
\(x\) - 2 + 7 = 3.(-9)
\(x\) - 2 + 7 = - 27
\(x\) = - 27 - 7 + 2
\(x\) = - 34 + 2
\(x\) = - 32
Vậy \(x=-32\)
Bài 1
c; - 2\(x\) + 5 = 7
- 2\(x\) = 7 - 5
- 2\(x\) = - 2
\(x\) = -2 : (-2)
\(x\) = - 1
Vậy \(x\) = - 1
a) y + 3/7 x 21/9 = 5
y + 3/7 x 7/3 = 5
y + 1 = 5
y = 4
b) y x 3/5 - 1/2 = 4/5
y x 3/5 = 4/5 + 1/2
y x 3/5 = 13/10
y = 13/6
c) 9/8 - y + 2/5 = 1/4
y - 2/5 = 9 /8 - 1/4
y - 2/5 = 7/8
y = 51/40
d) y - 6/5 : 2/3 = 5/6
y - 9/5 = 5/6
y = 79/30
e) y : 7/8 + 3/4 = 7/4
y : 7/8 = 1
y = 7/8